THE IMPACT OF SCHWARTZ MODEL ON IRAQI EFL FIFTH GRADE LITERARY STUDENTS’ ACHIEVEMENT IN RHETORIC - Yassin Habib Muharram Abbas , Dr. Mohammed Shaker Nasser Al-Rubaie , Dr. Riyadh Obaid Hataf Al-Khafaji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to investigate the effect of the Schwartz model on the literary achievement of fifth-grade students in rhetoric. The study depends on the experimental design as a methodology for conducting the research, which included an independent variable (Schwartz model, the usual method) and a dependent variable (academic achievement). The researchers use experimental design with partial control to adjust the research variables. Before starting the application of the experiment, the researchers equalize between the two groups in some of the variables that may influence the study and bring inaccurate results of the experiment. The study adopted a pre-test treatment post-test design. It is hypothesized that there is no significant difference between the mean score of the students’ achievement who are taught by the Schwartz Model and that of the students taught by the recommended method from the ministry of education. The test results were analyzed statistically, and it was found out that the achievement of the subjects of the experimental group was better than that of the subjects of the control group.